The Influence Factor For The Successful Implementation Of Cleaner Production : A Review - Yusup, Muhamad Zaki; Wan Mahmood, Wan Hasrulnizzam; Salleh, Mohd Rizal; Muhamad, Mohd Razali (Penerbit UTM Press, 2014)
-